The Author Inside: Celebrity Photography 1840‒1902 - Audrey Doussot (Cahiers Victoriens et Edouardiens)
The invention and popularization of photography in the nineteenth century revolutionized portraiture. From the beginnings, many writers posed in front of the camera to have their portraits captured by the successive developments of the daguerreotype, the carte-de-visite and other cheaper as well as more practical and portable photographic processes that brought portraiture outside the professional studio. A simultaneous growing interest in literary celebrities and the places related to them and their works led photographers to produce pictures of writers in their habitat, including pictures that were disseminated among the public through collectibles or publications. The representation of interiors in most photographic portraits of Victorian and Edwardian writers appears as a key element contributing to constructing the writer as a sociocultural type and a public figure. What can be perceived, at first, as a mere backdrop to the representation of a human being can actually reveal much about the fashioning of an author’s literary identity through images. Portraits of Charles Dickens or George Bernard Shaw, for instance, testify to the importance of staging and accessories when seeking to construct authors’ images and to depict their universe as a materialization of their character and psychological interiority.